Scanning Electron Microscopic Evaluation of Smear Layer Removal and Estimation of Dentin Microhardness Using TRITON Endodontic Irrigant: An In Vitro Study - Nawfal A. Zakaria; Mohammed Khudair (Erbil Dental Journal)
Background and objectives: Irrigation is essential in endodontic therapy, and traditional irrigation was done with NAOCl and EDTA to remove the smear layer and clean the canal, but it had several difficulties. Many solutions, such as Smearoff, Qmix and MTAD, are available as a single irrigant solution to disinfect and remove the smear layer. TRITON is a revolutionary two-in-one irrigant that can both remove smear layer and disinfect the canal. This study aims to evaluate the effect of Triton on smear layer removal and compare it with Qmix and conventional NaOCl and EDTA irrigation protocols.